IMPLEMENTATION OF SEA PORT MANAGEMENT POLICIES BY THE PORT MASTER AND CLASS 1 BITUNG PORT AUTHORITY OFFICE - Sanchez Roy Tantu; Theodorus Pangalila; Jetty E. H. Mokat (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the implementation of the policy on duties and functions of seaport management by the Bitung Class I Harbormaster and Port Authority Office (KSOP) and to identify the determinants influencing the implementation of the policy. This study uses a qualitative approach with descriptive methods. The research location was at the Bitung Class I KSOP. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Research informants consisted of KSOP officials, operational employees, port service users, and other related parties. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, while data validity was tested through source and technique triangulation. The results of the study indicate that the implementation of the policy on duties and functions of seaport management by the Bitung Class I KSOP has not been running optimally. In its regulatory function, there are still inconsistencies in the application of regulations and delays in port administration processes. In its supervisory function, limited human resources and supporting facilities have resulted in less than optimal supervision of port activities. Meanwhile, in the function of port service providers, the quality of task implementation has not fully met the principles of speed, accuracy, transparency, and responsiveness as mandated by Law Number 25 of 2009. The determinant factors that influence policy implementation include aspects of communication, human resources, apparatus disposition, and bureaucratic structure. This study concludes that the effectiveness of the implementation of seaport management policies at KSOP Class I Bitung requires strengthening inter-agency coordination, increasing human resource capacity, simplifying administrative procedures, and optimizing technology-based work systems.